Risk Factors for Suicidal Behaviour in Individuals on Disability Pension Due to Common Mental Disorders - A Nationwide Register-Based Prospective Cohort Study in Sweden - Rahman, Syed (Public Library of Science, 2014)
BACKGROUND: Common mental disorders (CMD) have become one of the leading causes for disability pension (DP). Studies on predictors of adverse health outcome following DP are sparse. This study aimed to examine the association of different socio-demographic factors and health care consumption with subsequent suicidal behaviour among individuals on DP due to CMD. METHOD: This is a population-based prospective cohort study based on register data. All individuals aged 18–64 years, living in Sweden on 31-Dec-2004 who in 2005 were on DP due to CMD (N = 46 745) were followed regarding suicide attempt and suicide (2006–10). Univariate and multivariate hazard ratios (HR) and 95% confidence intervals (CI) for suicidal behaviour were estimated by Cox regression. RESULTS: During the five-year follow-up, 1 046 (2.2%) and 210 (0.4%) individuals attempted and committed suicide, respectively. Multivariate analyses showed that young age (18–24 years) and low education predicted suicide attempt, while living alone was associated with both higher suicide attempt and suicide (range of HRs 1.23 to 1.68). Combined prescription of antidepressants with anxiolytics during 2005 and inpatient care due to mental diagnoses or suicide attempt (2001–05) were strongly associated with suicide attempt and suicide (range of HRs 1.3 to 4.9), while inpatient care due to somatic diagnoses and specialized outpatient care due to mental diagnoses during 2001–05 only predicted suicide attempt (HR 1.45; 95% CI: 1.3–1.7; HR 1.30; 95% CI: 1.1–1.7). CONCLUSIONS: Along with socio-demographic factors, it is very important to consider type of previous healthcare use and medication history when designing further research or intervention aiming at individuals on DP due to CMD. Further research is warranted to investigate both characteristics of disability pension due to CMD, like duration, diagnoses and grade as well as mechanisms to subsequent suicidal behavior, taking potential gender differences into consideration.